Positive Politeness Used By The Characters In The Movie Entitled Luck - Ni Wayan Pipit Pranika; I Gusti Agung Sri Rwa Jayantini (Denpasar Institute, 2023)
This study focuses on positive politeness strategy. The purpose of this study is to find out the used of positive politeness strategy by the main characters. The data are taken from movie entitled Luck. The analysis was using descriptive qualitative method and the theory from Brown and Levinson 1987 by watching, observing, and note taking the data. The result showed that Notice, Attend to H (his interest, wants needs, goods) There are four data, in Exaggerate (Interest, Approval, Sympathy with H) there is one data, in Intensify Interest to H there is one data, in Use In-group Identity Markers there are three data, in Seek Agreement there are five data, in Avoid Disagreement there are three data, in Presuppose/Raise/Assert Common Ground there are two data, in Joke there is one data, in Assert or Presuppose S’s Knowledge of and Concern for H’s Wants there is one data, in Offer, promise there is one data, in Be Optimistic there is one data, in Include Both S and H in the Activity there are two data, in Give or Ask Reason there are four data, in Assume or Assert Reciprocity there is one data, in Give Gifts to H Goods, Sympathy, Understanding, Cooperation there are four data